2022
DOI: 10.12911/22998993/144785
|View full text |Cite
|
Sign up to set email alerts
|

An Improve Performance of Geospatial Model to Access the Tidal Flood Impact on Land Use by Evaluating Sea Level Rise and Land Subsidence Parameters

Abstract: In the 20 th century, climate change caused an increase in temperature that accelerated the rate of sea level. Sea level rise and land subsidence threaten densely populated coastal areas as well as lowlands because they cause tidal flooding. Tidal floods occur every year due to an increase in sea level rise and land subsidence. The lack of information on this phenomenon causes delays in disaster mitigation, leading to serious problems. This study was conducted to predict the area of tidal flood inundation on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Climate change adaptation strategies must be woven into disaster response plans to address the escalating frequency and intensity of floods [10]. Integrating climate resilience measures can enhance the effectiveness of disaster preparedness and public health interventions.…”
Section: Climate Change Adaptationmentioning
confidence: 99%
“…Climate change adaptation strategies must be woven into disaster response plans to address the escalating frequency and intensity of floods [10]. Integrating climate resilience measures can enhance the effectiveness of disaster preparedness and public health interventions.…”
Section: Climate Change Adaptationmentioning
confidence: 99%
“…The latest study also identified that tidal flooding had enlarged yearly. In 2020 alone, the tidal flood coverage area was 783.99 hectares [4], while other research asserted that tidal floods had affected 50% of Pekalongan city [3].…”
Section: Introductionmentioning
confidence: 97%
“…The latest global catastrophe is caused by climate change and global warming. The rise in sea level, which causes floods and tidal floods, is one of the effects of climate change that is readily apparent [3] [4]. The flood discharge, water channel hydraulics, water reservoir volume, and the suitable pump capacity must all be determined through analysis [5].…”
Section: Introduction 1backgroundmentioning
confidence: 99%